A learning organization in the light of selected research results - Kapatsevich, Anastasiya (Management and Administration Journal, 2019)
The aim of the study is to present the concept of „a learning organization” and its meaning and role in modern society. The study consists of four parts. The first part presents the concept of a learning organization. The second part takes into consideration the literature and the problem that exists according to the authors’ beliefs.In the third part, the research and comments are presented. Based on the analysis of the selected results of international and Polish research, the main factors influencing the functioning and development of the organization are presented, the learning process in such organiza-tions is analyzed, and the main advantages and possibilities of the learning organization are highlighted. The results obtained in these studies were verified using quantitative methods. At the end of the article, the conclusions and recommendations are presented.